A facile alternative strategy of upcycling mixed plastic waste into vitrimers - Ng, Joseph Kok Wei (2023)
Chemical depolymerization has been identified as a promising approach towards recycling of plastic waste. However, complete depolymerization may be energy intensive with complications in purification. In this work, we have demonstrated upcycling of mixed plastic waste comprising a mixture of polyester, polyamide, and polyurethane through a reprocessable vitrimer of the depolymerized oligomers. Using poly(ethylene terephthalate) (PET) as a model polymer, we first demonstrated partial controlled depolymerization, using glycerol as a cleaving agent, to obtain branched PET oligomers. Recovered PET (RPET) oligomer was then used as a feedstock to produce a crosslinked yet reprocessable vitrimer (vRPET) despite having a wide molecular weight distribution using a solventless melt processing approach. Crosslinking and dynamic interactions were observed through rheology and dynamic mechanical analysis (DMA). Tensile mechanical studies showed no noticeable decrease in mechanical strength over multiple repeated melt processing cycles. Consequently, we have clearly demonstrated the applicability of the above method to upcycle mixed plastic wastes into vitrimers and reprocessable composites. This work also afforded insights into a potentially viable alternative route for utilization of depolymerized plastic/mixed plastic waste into crosslinked vitrimer resins manifesting excellent mechanical strength, while remaining reprocessable/ recyclable for cyclical lifetime use.